Changes in drinking patterns during and after pregnancy among mothers of children with fetal alcohol syndrome: A study in three districts of South Africa. (1st November 2016) - Urban, Michael F.; Olivier, Leana; Louw, Jacobus G.; Lombard, Chanelle; Viljoen, Denis L.; Scorgie, Fiona; Chersich, Matthew F.
Highlights: A minority of South African mothers to children with P/FAS stop drinking in pregnancy. Cessation of drinking, and of recidivism post-pregnancy, varies between sites. Despite recidivism, stopping in pregnancy is associated with abstinence >7 years later. Selective interventions should target pregnancy but extend into the puerperium. Abstract: Background: Mixed ancestry populations in South Africa have amongst the highest rates of fetal alcohol syndrome (FAS) worldwide. Defining the drinking patterns of women with a FAS child guides FAS preventive interventions. Methods: Data were drawn from FAS prevalence surveys conducted in three districts: Witzenberg (Cape Winelands), Frances Baard (inland mining town) and Saldanha Bay (coastal towns). 156 mothers and 50 proxy informants of school-entry children diagnosed with FAS and partial-FAS were interviewed, and compared with 55 controls recruited in Saldanha Bay. Results: Study participants were of low socio-economic status (SES), and a majority of children were either in foster care (12%) or had been cared for by relatives for long periods (44%). Of cases, 123/160 (77%) reported current drinking, similar between sites. During pregnancy, only 35% (49/139) of cases had stopped drinking, varying between sites (from 21% to 54% in chronological order of surveys; p < 0.001), while 6% (7/109) increased drinking. Though many women who stopped in pregnancy resumed postpartum, cessation in pregnancy was strongly associated with discontinuation in the long run (OR = 3.3; 95%CI = 1.2–8.9; p = 0.005). At interview, 36% of cases (54/151) and 18% of controls (9/51) were at risk of an alcohol-exposed pregnancy (p = 0.02). Median maternal mass of cases was 22 kg lower than controls, with 20% being underweight and 14% microcephalic. Conclusions: Increasing rates of drinking cessation during pregnancy over time suggest rising awareness of FAS. Cessation is associated with recidivism after pregnancy but also with reduced long-term drinking. Interventions should target alcohol abstinence in pregnancy, but extend into the puerperium.